Knowledge, awareness, and practices among consumers regarding trans-fat: A cross-sectional study - Poonam Khanna; Sonu Goel; Rachita Jain; Arshdeep Singh; Mahendra Pratap Singh (Wolters Kluwer Medknow Publications, 2022)
Introduction: Processed and preserved food items are the major source of dietary trans fat. Despite various legal provision, public awareness toward trans fats are limited. Objective: To examine the awareness of participants about various aspects of trans fats and improving their knowledge through education. Methods: A cross sectional pre- and posttest survey was conducted online through a webinar. The questionnaire has 11 questions about trans fats. Received responses were coded. Mean and frequency of continuous data were calculated. Chi-square or t-test were used to find the difference in pre and posttest. Results: Eighty five out of 95 participants completed both pre- and posttest. The scores for each question were compared to find out awareness improvement. The question based on FSSAI showed 57% improvement while 50% in case of World Health Organization's REPLACE initiative. The difference of mean score of pretest (7.57 ± 1.8) and posttest (9.22 ± 1.37) was statistically significant. Conclusion: Nutrition education and proper labelling of food items can improve the knowledge about food ingredients and food purchasing patterns. Proper enforcement and monitoring of food items labeling guidelines can be recommended.